Sex differences in human mate preferences vary across sex ratios. Issue 1955 (28th July 2021) - Walter, Kathryn V.; Conroy-Beam, Daniel; Buss, David M.; Asao, Kelly; Sorokowska, Agnieszka; Sorokowski, Piotr; Aavik, Toivo; Akello, Grace; Alhabahba, Mohammad Madallh; Alm, Charlotte; Amjad, Naumana; Anjum, Afifa; et al.
Abstract : A wide range of literature connects sex ratio and mating behaviours in non-human animals. However, research examining sex ratio and human mating is limited in scope. Prior work has examined the relationship between sex ratio and desire for short-term, uncommitted mating as well as outcomes such as marriage and divorce rates. Less empirical attention has been directed towards the relationship between sex ratio and mate preferences, despite the importance of mate preferences in the human mating literature. To address this gap, we examined sex ratio's relationship to the variation in preferences for attractiveness, resources, kindness, intelligence and health in a long-term mate across 45 countries ( n = 14 487). We predicted that mate preferences would vary according to relative power of choice on the mating market, with increased power derived from having relatively few competitors and numerous potential mates. We found that each sex tended to report more demanding preferences for attractiveness and resources where the opposite sex was abundant, compared to where the opposite sex was scarce. This pattern dovetails with those found for mating strategies in humans and mate preferences across species, highlighting the importance of sex ratio for understanding variation in human mate preferences.